2016
DOI: 10.14295/cs.v7i1.1332
|View full text |Cite
|
Sign up to set email alerts
|

Adubação potássica na produção e qualidade pós-colheita de goiaba ‘Paluma’ no semiárido potiguar

Abstract: The aim of this study was to evaluate the effect of potassium fertilization on yield and final quality of guava fruit variety ‘Paluma’, grown at the Irrigated District of Baixo Açu-RN, Brazil. The experimental was carried out in a completelyrandomized blocks design in split plot with five treatments (0, 0.5, 1.0, 1.5 and 2.0 kg K2O plant-1) with four repetitions. The subplots were composed of two harvest seasons and the following characteristics were evaluated: number of fruits, commercial production, total pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
1
1
4
Order By: Relevance
“…The values of production were high when compared to those obtained by Alencar et al (2016), who reported production of 30 kg per plant for irrigated 'Paluma' guava in the semi-arid region of Rio Grande do Norte state. Considering the average quantity of 416.66 plants per hectare, the fruit yield presented was above the national average, which is 24.9 t ha -1 (IBGE, 2021), with the exception of cultivation without rootstock when irrigated with 40 and 60% ETc, which resulted in fruit yield of 16.83 and 23.71 t ha -1 , respectively.…”
Section: Table 1 Summary Of Analysis Of Variance Of the Variables Ana...contrasting
confidence: 53%
“…The values of production were high when compared to those obtained by Alencar et al (2016), who reported production of 30 kg per plant for irrigated 'Paluma' guava in the semi-arid region of Rio Grande do Norte state. Considering the average quantity of 416.66 plants per hectare, the fruit yield presented was above the national average, which is 24.9 t ha -1 (IBGE, 2021), with the exception of cultivation without rootstock when irrigated with 40 and 60% ETc, which resulted in fruit yield of 16.83 and 23.71 t ha -1 , respectively.…”
Section: Table 1 Summary Of Analysis Of Variance Of the Variables Ana...contrasting
confidence: 53%
“…Esses valores estão muito aquém dos 232 frutos planta -1 obtidos com a Rev. Ceres, Viçosa, v. 66, n.1, p. 054-062, jan/fev, 2019 dose de 2 kg planta -1 de K 2 O por Alencar et al (2016), utilizando o mesmo cultivar de goiaba, em plantas com três anos de idade. Entretanto, as plantas do presente trabalho tinham 22 meses de idade, o que pode justificar essa diferença na produção de frutos.…”
Section: Resultsunclassified
“…Entretanto, a adubação com doses de K 2 O acima das máximas estimadas inibiu a capacidade produtiva da goiabeira 'Paluma', em ambas as situações, por causa de o K induzir deficiência de Ca e Mg nas plantas, quando em concentrações elevadas no solo (Malavolta et al, 1997;Marschner, 2012). Esses valores estão bem abaixo dos 55,7 kg planta -1 produzidos com a dose de 330 g planta -1 ano -1 de K 2 O, na primeira safra, em goiabeira 'Paluma' irrigada (Alencar et al, 2016) e assemelham-se aos 25 kg planta -1 de frutos de goiaba na dose 400 g planta -1 de K 2 O (Lima et al, 2008). Esses resultados corroboram os de Souza et al (2012) e Souza et al (2014) ao concluírem que a goiabeira é muito exigente em K, por isso, a adubação com esse macronutriente justifica seu efeito positivo no crescimento vegetativo e na produção de frutos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Guava seedlings were planted in August 2019 at each farm, where phosphorus and manure were used as basal fertilizers. The cultivar Paluma was used because it is a common guava tree planted in the Brazilian semiarid region, due to its high productivity and versatility for fresh and industrial consumption (ALENCAR et al, 2016). The experimental guava orchards were daily irrigated, and guava trees were about 1m in height during the current evaluation.…”
Section: Data Collectionmentioning
confidence: 99%